Tectonic, hydrogeologic, and climatic controls on Late Holocene dune formation, China Lake basin, Indian Wells Valley, California, USA. (March 2022) - Lancaster, Nicholas; Bacon, Steven N.; Bullard, Thomas F.; Neudorf, Christina M.; Keen-Zebert, Amanda K.; Decker, David L.; Boggs, Matthew L.
Abstract: Analysis of patterns of faulting and hydrogeology, stratigraphic and sedimentologic studies, and luminescence dating of aeolian deposits in China Lake basin provide new perspectives on the origins and development of Late Holocene dunes and sand ramps in the seismically active Indian Wells Valley of eastern California. Aeolian dune and sand sheet deposits were sourced from alluvial material derived from granitic rocks of the south-eastern Sierra Nevada and are concentrated in areas with sand-stabilizing phreatophyte vegetation influenced by high groundwater levels along the active oblique-normal Little Lake and Paxton Ranch faults, which locally form barriers to groundwater flow. Three episodes of sand accumulation are recognized (2.1 ± 0.1 to 2.0 ± 0.1 ka, 1.8 ± 0.2 to 1.6 ± 0.2 ka, and 1.2 ± 0.1 to 0.9 ± 0.1 ka) during conditions in which sediment supplied to the basin during periods of enhanced rainfall and runoff was subsequently reworked by wind into dunes and sand ramps at the transition to more arid periods. Understanding the role tectonics plays in influencing the hydrogeology of seismically active lake basins provides insights to accurately interpret landscape evolution and any inferences made on past hydroclimate variability in a region.